Pyrolytic conversion of perennial grasses and woody shrubs to energy and chemicals - Rada Arias, Eduardo Alberto (2019)
Spartina argentinensis, Panicum prionitis, and Arundo donax are perennial grasses and Geofroea decorticans is a shrub, all of which grow under adverse conditions in the Litoral region in Argentina. The pyrolytic conversion of these biomasses was studied at 550 °C in a fxed bed reactor during 30 min under N2 fow with a 20 °C min−1 heating ramp starting at room temperature. The main products were liquid, two phases (aqueous and oil) being observed with the aqueous phasesbeing the most important in all the cases (yields from 29.2 to 45.7 wt%). The highest yield for an oil phase (18 wt%) was observed with the shrub and the yield of gases and chars were similar in all the cases. By means of sequential vacuum distillation I was possible to selectively separate water, methanol and acetic acid which were present in the aqueous phases, thus increasing the concentration of high value compounds such as ketones, phenols and furans in the residual fraction. The concentration of phenolic compounds in the residual fraction was 60% higher than the initial one in the aqueous phase. The oil phase mainly contained phenols, ketones and acids with high molecular weight. According to these results, these biomasses can be considered as a source of energy, fuels or chemicals, and it is possible to propose a methodology to upgrade the aqueous fractions in pyrolysis liquids.